Iris Obstruction Following PRESERFLO Microshunt Implantation and Surgical Management. Issue 8 (6th August 2022) - Trigaux, Céline; Steindor, Friedrich A.; Spaniol, Kristina; Geerling, Gerd; Borrelli, Maria
Abstract : Purpose: The aim was to present a case of lumen obstruction after implantation of microshunt with subconjunctival drainage and subsequent management. Case Report: A 56-year-old male with primary open angle glaucoma underwent uneventful PRESERFLO MicroShunt (PMS) implantation in both eyes. Five months after surgery the patient presented with an intraocular pressure (IOP) of 26 mm Hg in the right eye because of iris obstruction. Results: The iris fibers were severed and removed surgically to free the lumen. Follow-up showed a normalized IOP of 10 mm Hg and a free lumen. Conclusion: Uncontrolled IOP because of iris obstruction following PMS was addressed by surgical removal of iris fibers at the lumen entrance without the need for tube repositioning.